Changes in inhibitory control, craving and affect after yoga vs. aerobic exercise among smokers with nicotine dependence - Kim, Hyungsook; Kim, Jingu; Woo, Minjung; Kim, Teri (Frontiers in Psychiatry, 2022)
Objectives: This study investigated the acute effects of yoga and aerobic exercise on response inhibition and the underlying neural mechanisms in individuals with nicotine dependence, along with changes in craving and affect. Methods: Study participants included 30 yoga-naïve adult smokers with moderate-to-high nicotine dependence. Based on a within-subjects design, all participants participated in three experimental sessions: baseline, 30-min yoga, and 30-min aerobic exercise; one session was conducted per day. The pre- and post-exercise Questionnaire of Smoking Urges and the Visual Analogue Scale were used to measure cigarette craving, and the Positive and Negative Affect Schedule was used to assess affective change. For cognitive measurement of inhibition, participants performed a Go/Nogo task consisting of Smoking-Go, Smoking-Nogo, Neutral-Go, and Neutral-Nogo stimulus conditions. Neuroelectric data were collected and the event-related potential (ERP) N2 and P3 amplitudes and latencies were analyzed. Results: Both yoga and aerobic exercise significantly reduced negative affect, whereas a reduction in craving was only observed after yoga. ERP results indicated that the P3 amplitudes after yoga were lower than those after aerobic exercise, suggesting increased neural efficiency after yoga, with reduced neural activity while maintaining the same level of cognitive performance as aerobic exercise. Conclusions: As yoga and aerobic exercise were equally effective in attenuating negative affect, smokers may expect greater benefits from yoga in craving reduction and inhibitory control with less physical and cognitive effort. We also believe that video-based yoga practice may provide additional benefits to these effects, reaching a large number of smokers in a non-face-to-face manner.